Down payment policy and economic fluctuations in a heterogeneous DSGE model: the case of China - He, Yiyao (International Journal of Strategic Property Management, 2019)
Motivated by the observation that the down payment policy in China is government-controlled and pro-cyclical based on the housing market, I construct a heterogeneous DSGE model to study the relationship between China’s down payment policy, property tax, and economic fluctuations. The results indicate that an increasing down payment ratio suppresses the speculative belief and decreases household’s housing demand. This in turn pulls housing prices down and smoothes the economic fluctuations. By way of counterfactual exercises, I also find that the down payment policy and the property tax can be substitutes for each other. If there is an active down payment policy, the implementation of property tax shall be prudently deliberated by the Chinese government.